POLA KARIES PENDERITA KARSINOMA NASOFARING YANG MEMPEROLEH TERAPI RADIASI - Ratna Meidyawati; Edi Hartini Sundoro; R. Susworo (Faculty of Dentistry, Universitas Indonesia, 2015)
Therapy of radiation is chosen therapy for oral cancer especially Carcininoma Nasopharynx, however, often caused changes in normal tissue in the oral cavity. Based on the anamneses of the patient, they have dry mouth since the disturbance of the function of parotid salivary gland has causing the saliva amount become lower. This condition can encourage the caries process. From all of the five cases occurred after the radiation between one month until six years the time, extended damage is seen, demineralization with a small cavity, and discoloring teeth color into brown.